PRAKTIK JUAL BELI MAKANAN ONLINE DI FACEBOOK DALAM PERSPEKTIF ETIKA BISNIS ISLAM DESA BANATO REJO - Liwaul Hikmah; Muh. Irwan T; Muh. Bahrul Afif (J-Alif : Jurnal Penelitian Hukum Ekonomi Syariah dan Budaya Islam, 2025)
This study aims to examine the practices of online food trading on Facebook and how Islamic business ethics are applied within those practices in Banato Rejo Village, Tapango District. This research uses a qualitative approach with a field research method. Data collection techniques include observation, direct interviews with business actors and consumers, and documentation. The data were analyzed inductively, emphasizing a deep understanding of the online food trading practices on Facebook. The results show that such practices provide various benefits for both sellers and buyers. Sellers experience an increase in orders and easier promotion, while buyers benefit from the convenience of ordering food quickly and practically without leaving their homes. However, there are still some drawbacks, such as unilateral cancellations by buyers, delayed deliveries, and slow seller responses. From the perspective of Islamic business ethics, most business actors have applied basic principles such as honesty, responsibility, trustworthiness, and kindness to consumers. This is reflected in their efforts to maintain food quality, be courteous to customers, and acknowledge and correct service errors. Nevertheless, shortcomings remain, including a lack of debt recording and suboptimal service during peak order times.